O-002 Initial Clinical Experience with the ADAPT technique: A Direct Aspiration first Pass Technique for Stroke Thrombectomy. (14th July 2013) - Turk, A; Spiotta, A; Frei, D; Mocco, J; Baxter, B; Siddiqui, A; Mokin, M; Dewan, M; Turner, R; Hawk, H; Miranpuri, B; Chaudry, I
Abstract : Background: The development of new revascularisation devices has improved recanalisation rates and time, but not clinical outcomes. We report our initial results with a new technique utilising a direct aspiration first pass technique with large bore aspiration catheter as the primary method for vessel recanalisation. Methods: A retrospective chart review of 18 patients at 5 institutions was performed on patients where the ADAPT technique was utilised. The data represents the initial experience with this technique. Results: The ADAPT technique alone was successful in 2/3 cases, although 4 cases had large downstream emboli that required additional aspiration. Four cases required the additional use of a stent retriever and one case required the addition of a Penumbra aspiration separator to achieve recanalisation. The average time from groin puncture to at least TICI 2b recanalisation was 30 minutes and all cases were successfully revascularised. TICI 3 recanalisation was achieved 72% of the time. On average, patients presented with an admitting NIHSS of 16.4 and improved to NIHSS of 3.1 by the time of discharge. There were no procedural complications. Discussion: This initial experience highlights the importance of the technique with which new stroke thrombectomy devices are used may be as crucial as the device itself. The ADAPT technique is a simple cost effective method that is leading us to re-think our approach to acute ischaemic stroke thrombectomy by simply utilising the latest generation of large bore aspiration catheters independently to achieve excellent angiographic and clinical outcomes. Disclosures: A. Turk: 1; C; Penumbra, Covidien, Microvention. A. Spiotta: None. D. Frei: None. J. Mocco: None. B. Baxter: None. A. Siddiqui: None. M. Mokin: None. M. Dewan: None. R. Turner: None. H. Hawk: None. B. Miranpuri: None. I. Chaudry: 1; C; Penumbra, Covidien, Microvention.